A region of increased attention. Why is Japan interested in Central Asia? (Eurasian Scientific Herald, 2025)
This article examines the increasingly changing geopolitical landscape of the Central Asian region. In particular, it examines Japan’s strategy in the region, its policy achievements, and its future challenges. Japan’s Central Asian policy is analyzed in the context of Russian-Japanese and Japanese-Western relations. Tokyo’s activity in the region has not been characterized so much by high-profile initiatives but by the gradual development of practical projects of primarily economic interest. Japan represents an alternative for Central Asian countries compared to countries such as China and Russia. Japan’s aid is provided through official development assistance channels and is aimed at modernizing Soviet-era infrastructure. ODA reflects the complex nature of Japan’s foreign policy, which combines a strategy based on national interests, a desire to implement liberal values, and an emphasis on a common Asian identity with the countries of the region.